2014
DOI: 10.1155/2014/828102
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs for Resistance toSclerotinia sclerotiorumin Carioca Common Bean by theMoving AwayMethod

Abstract: The aim of this study was to use multiple DNA markers for detection of QTLs related to resistance to white mold in an F2 population of common bean evaluated by the straw test method. The DNA from 186 F2 plants and from the parents was extracted for genotypic evaluation using SSR, AFLP, and SRAP markers. For phenotypic analysis, 186 F2:4 progenies and ten lines were evaluated, in a 14 × 14 triple lattice experimental design. The adjusted mean values of the F2:4 progenies were used for identification of QTLs by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(36 reference statements)
0
7
0
1
Order By: Relevance
“…Escape mechanisms and physiological resistance mechanisms are quantitatively inherited and controlled by QTLs (quantitative trait loci) to both small and large effect (Miklas et al, 2013;Mkwaila et al, 2011;Soule et al, 2011;Lara et al, 2014).…”
mentioning
confidence: 99%
“…Escape mechanisms and physiological resistance mechanisms are quantitatively inherited and controlled by QTLs (quantitative trait loci) to both small and large effect (Miklas et al, 2013;Mkwaila et al, 2011;Soule et al, 2011;Lara et al, 2014).…”
mentioning
confidence: 99%
“…In a study developed by Lara et al (2014Lara et al ( , 2015, ME1 was found to be located 0.82 and 0.29 cM from a QTL with 71.37 and 0.55% heritability by the straw test and oxalic acid evaluation methods, respectively. This QTL acts to increase resistance to white mold.…”
Section: Discussionmentioning
confidence: 97%
“…Haggard (2007) identified this marker associated with resistance to white mold by straw test in GL6. By using both the straw test and reaction to oxalic acid, Lara et al (2014Lara et al ( , 2015 used the mapping population obtained from a cross between CNFC 9506 and RP-2 and identified the markers BM184 and BM187 associated with the most significant QTL, with high heritability. However, these markers contribute to reduce resistance and are distant from each other at 43.84 cM by the oxalic acid method.…”
Section: Discussionmentioning
confidence: 99%
“…Real data from QTL searches for resistance to white mold disease (Sclerotinia sclerotiorum) in the common bean were obtained from Lara et al (2014). In all, 186 progenies of a F 2:4 common bean population were obtained by crossing the CNFC 9506 and RP-2 lines, and were genotyped with 59 markers: 17 simple sequence repeats, 31 amplified fragment length polymorphisms, and 11 sequence-related amplified polymorphisms.…”
Section: Real Datamentioning
confidence: 99%
“…Using Method I, no marker was important ( Figure 7) Lara et al (2014), 17 of the 59 markers identified QTLs for resistance to white mold (above the red line) according to the Wald test (Figure 8). …”
Section: Real Datamentioning
confidence: 99%